COMPREHENDING EVIDENCE BASED AYURVEDA (International Journal of Ayurveda and Pharma Research, 2015)
Science could be best defined as pure unbiased knowledge which possess a set of concrete rationale which when pertinently applied in accordance to the circumstance, would yield accurate intended results permanently. Ayurveda is such a Science of life which encompasses in-depth scientific theorems and principles which are evolved by close and constant experimentation in human beings in multiple ways (the methodologies of which are technically described in medical treatises) and best scientifically validated and approved constantly by the experts for the last many centuries. For this reason, it is undoubtedly clear that this scientifically validated medical theories and principles which are verified successful in every era is the best pertinent evidence base to precisely guide ayurvedic medical practice and research.